The impact of mental accounting on financial management with financial literacy as a moderator: a study on microtransaction buyers in online games - Fauzilana, Erdana Dwiyatna; Maulana, Agus (Akuntansiku, 2025)
This study aims to analyze the influence of accounting mentality on financial management, with financial literacy as a moderating variable, on microtransaction buyers in online games. This study is based on the phenomenon of increasing microtransactions in online games that can affect individual financial management behavior. With an explanatory quantitative approach, data were collected through questionnaires to 100 respondents aged 18–35 years who had made microtransactions. The analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the relationship between variables. The results showed that accounting mentality had a significant influence on financial management. However, financial literacy was not proven to strengthen the influence of accounting mentality on financial management. This study provides insight that although accounting mentality helps individuals manage their finances, increasing financial literacy alone does not always have an impact on the effectiveness of the relationship, especially in the context of microtransactions.